Urgent Carotid Surgery: Is It Still out of Debate?. (19th March 2012) - Battocchio, C.; Fantozzi, C.; Rizzo, L.; Persiani, F.; Raffa, S.; Taurino, M.
Abstract : Patients with symptomatic tight carotid stenosis have an increased short-time risk of stroke and an increased long-term risk of ischaemic vascular events compared with the general population. The aim of this study is to assess the safety, efficacy, and limitations of urgent CEA or CAS, in patients with carotid stenosis greater than 70% and clinically characterized by recurrent TIA or brain damage following a stroke (<2.5 cm). This study involved 28 patients divided into two groups. Group A consisted of sixteen patients who had undergone CEA, and group B consisted of twelve patients who had undergone CAS. Primary endpoints were mortality, neurological morbidity (by NIHSS) and postoperative hemorrhagic cerebral conversion, at 30 days. Ten patients (62.5%) of group A experienced an improvement in their initial neurological deficit while in 4 cases (26%) the deficit remained stable. Two cases of neurologic mortality are presented. At 1 month, 9 patients (75%) of group B experienced an improvement in their initial neurological deficit while 3 patients (25%) had a neurological impairment. Urgent or deferred surgical or endovascular treatment have a satisfactory outcome considering the profile in very high-risk patient population. Otherwise in selected patients CEA seems to be preferred to CAS.